Anticancer Activity of Key Lime, Citrus aurantifolia - Narang, Nithithep; Jiraungkoorskul, Wannee (Pharmacognosy Reviews)
Citrus aurantifolia (family: Rutaceae) is mainly used in daily consumption, in many cultural cuisines, and in juice production. It is widely used because of its antibacterial, anticancer, antidiabetic, antifungal, anti-hypertensive, anti-inflammation, anti-lipidemia, and antioxidant properties; moreover, it can protect heart, liver, bone, and prevent urinary diseases. Its secondary metabolites are alkaloids, carotenoids, coumarins, essential oils, flavonoids, phenolic acids, and triterpenoids. The other important constituents are apigenin, hesperetin, kaempferol, limonoids, quercetin, naringenin, nobiletin, and rutin, all of these contribute to its remedial properties. The scientific searching platforms were used for publications from 1990 to present. The abstracts and titles were screened, and the full-text articles were selected. The present review is up-to-date of the phytochemical property of C. aurantifolia to provide a reference for further study.
Keywords: Cancer; Citrus aurantifolia; herb; lime; phytochemical substance; plant